Pandemic 19 On Children's Rights In Abroad Families (Study in Pringtutul Hamlet , Kalisabuk Village, Kesugihan District, Cilacap District) - Faroqi, Moh. Ingam (Muhammadiyah University of Surabaya, 2023)
Corona virus or covid-19 is A spreading epidemic to several countries or continents and in general infected Lots human beings and impact on rights child in the family overseas, From the results his research that in Hamlet Pringtutul , it turns out Still There is right child who doesn't obtain her rights like right education , religious rights , rights social and rights health by parents consequence The Covid-19 pandemic , because factor economic , family , social or environmental , parents , schools , facilities , infrastructure and religion. As for effort family overseas to rights child For obtain religious rights , rights education , rights social and rights health that is First , parents role active to child related with matter formal and non - formal education as well as parents must help or direct child in study school so no wrong or wrong in learning . Third , nature love Darling or parental attention given to Â child more priority under the circumstances like this, especially in terms of religion, education , social and health so that more effective in reciting at the mosque / prayer room / TPQ, effective in learning at school , effective in interaction social , effective in guarding health so no There is difficulties and obstacles for kids at the moment Full Covid-19 pandemic limitations learning and religious activities at the mosque / musholla / TPQ always improved